The Friction and Wear Behaviours of Inconel 718 Superalloys at Elevated Temperature - Xu, Zhibiao; Lu, Zhijie; Zhang, Jun; Li, Dexiang; Liu, Jihua; Lin, Chengxiong (Frontiers in Materials, 2021)
Machine parts made of nickel-based alloys usually work in high-temperature service environments, such as aircraft turbines. The mechanical properties and antioxidant properties of materials tend to be reduced at high temperatures. Therefore, it is of great practical significance to reveal the wear mechanisms of materials at different temperatures. In the present investigation, the tribological behaviour of an Inconel 718 superalloy at different temperatures was investigated. First, the coefficient of friction (COF) curves obtained under different test conditions were analysed in detail to illustrate the dynamic change process of friction at high temperature. Next, the morphology of the wear surface, the surface morphology of friction pairs and the material transfer during friction were analysed via scanning electron microscopy (SEM), 3D morphology and energy dispersive spectroscopy (EDS) measurements to reveal the wear mechanisms of materials in a high-temperature environment. Finally, the microstructure of the cross section of the wear tracks was analysed by using optical microscopy (OM), electron back-scattered diffraction (EBSD), etc. to clarify the mechanisms of crack initiation and material removal. The results show that the friction properties of the Inconel 718 superalloy have some differences at different test temperatures. However, increasing the test temperature does not necessarily aggravate the wear of the material, but the oxidation of the wear surface during the friction process increases significantly. Besides, As the contact load increases, the thickness of the oxide layer and wear of the material increase simultaneously.